La moción de censura al Alcalde: especial atención a la posible suspensión del Pleno de votación (Asamblea. Revista parlamentaria de la Asamblea de Madrid, 2014)
This article examines the legal framework of the censure motion against Mayor, its background and the last reforms, paying special attention to the turncoat phenomenon, its implications and the different contingencies that could appear once the censure motion is signed by the councilors of the main opposition at the Town all. We also refer when the Mayor, his political group with or without support of other partners, try to avoid the voting provided in the electoral legislation claiming a turncoat case; and finally, we wonder in this article if a judge may suspend or adjourn provisionally the voting of the censure motion legally fixed to the 10th day after the censure motion signed and its implications at the Town Hall.
Keywords: Censure motion; turncoat phenomenon; voting; judge adjournment